SARS-COV-2-related immune-inflammatory thyroid disorders: facts and perspectives. (3rd July 2021) - Ruggeri, Rosaria Maddalena; Campennì, Alfredo; Deandreis, Desiree; Siracusa, Massimiliano; Tozzoli, Renato; Petranović Ovčariček, Petra; Giovanella, Luca
ABSTRACT: Introduction : During the COVID-19 pandemic thyroid gland alteration/dysfunction has been emerged as a possible endocrine complication. The present review is focused on inflammatory and autoimmune thyroid complications triggered by SARS-CoV-2 infection by searching through databases like MEDLINE and Scopus up to April 2021. Areas covered : Beside the occurrence of 'non-thyroidal illness' in severe clinical conditions, alterations of thyroid function and structure may occur during COVID-19 as a consequence of either direct or indirect effects of SARS-CoV-2 infection on the gland. On the one hand, SARS-CoV-2 uses ACE2 as a receptor to infect the host cells and ACE2 is highly expressed by follicular thyroid cells. On the other hand, COVID-19 is associated with a systemic inflammatory and immune response, involving Th1/Th17/Th2 lymphocytes and proinflammatory cytokines, which resembles the immune activation that occurs in immune-mediated thyroid diseases. COVID-19-related thyroid disorders include destructive thyroiditis and onset or relapse of autoimmune thyroid disorders, leading to a broad spectrum of thyroid dysfunction ranging from thyrotoxicosis to hypothyroidism, that may worsen COVID-19 clinical course and affect prognosis. Expert opinion : Physicians should be aware of the possible occurrence of thyroid dysfunction during and after SARS-CoV-2 infection. Further longitudinal studies are warranted to evaluate potential long-term sequelae.